Impacto de la reelección presidencial y la reforma política en las últimas elecciones (2006)
Constitutional reforms functionally speaking change compared with dogmatic ones, in just a simple view in the beginning could be a little insignificant – Electoral systems, control between and among powers, etc. but also and as a necessary consequence of the former elements just mentioned, to other institutional figures of the most important order like the ones that defend democratic values, division of powers or the need for a popular consensus for the construction of a political society. Under this scenario, the questions that motivated this statement are the following: How was the influence of the constitutional model of 1991, when talking about relationships between powers and public institutions in the subject of presidential power? How is this shown in the constitution of 1991? Which is the equality concept developed by the law and Colombian constitutional jurisprudence about re-election? Which are the practical effects of presidential re-election? Which was the effect of the political reform on the democracy?